EFEKTIVITAS PENDEKATAN SCIENTIFIC DALAM MATA KULIAH TRIGONOMETRI PADA MAHASISWA PENDIDIKAN MATEMATIKA IKIP PGRI PONTIANAK - Ardiawan, Yadi (UNIVERSITAS MUHAMMADIYAH METRO, 2015)
This study aimed to compare the results between student given learning mathematics instruction in the subject of trigonometry using a scientific approach and which does not use a scientific approach in the Program Studi Pendidikan Matematika PGRI Pontianak. The method used is the method of experimental research, the research form quasi-experimental design. This is because the educational research often are difficult to control manipulate all relevant variables. Results of this study are average student results provided scientific approach that is equal to 24.06 of a maximum score of 40. That is the percentage of scientific learning outcomes of 60.15% (quite enough). While the average student results are given learning without a scientific approach that is equal to 20.72 of a maximum score of 40. That is the percentage of learning outcomes without scientific amounted to 51.8% (relatively low). It can be concluded that the learning outcomes of students who are taught using a scientific approach is better than the learning outcomes of students who are taught not to use a scientific approach.